Are we so over smartwatches? Or can technology, fashion, and psychographic attributes sustain smartwatch usage? - Kamal Basha, Norazlyn; Cheng, Eugene Xi Aw; Hui, Stephanie Wen Chuah (Elsevier, 2022)
Smartwatch technology advancements have revolutionised a wide array of aspects of human life, ranging from communication to healthcare. As the smartwatch market moves beyond the initial adoption phase, there are questions regarding continued smartwatch usage. This study seeks to extend our understanding of sustained smartwatch usage. We propose and validate a framework that comprises technology-related features (i.e. perceived interactivity and perceived autonomy), fashion-related features (i.e. visual aesthetics and visibility), and psychographic factors (i.e. self-congruence and lifestyle congruence) as antecedents of value perception and smartwatch continuance intention. A quantitative survey was conducted with 275 smartwatch users, and the data were subjected to Partial Least Square-Structural Equation Modelling (PLS-SEM). The standard PLS-SEM findings, combined with importance performance map analysis (IPMA), indicate the relevance of perceived interactivity, perceived autonomy, visual aesthetics, self-congruence, and lifestyle congruence in determining value perception, which in turn positively influences continuance intention. A post-hoc multigroup analysis revealed the moderating effect of gender. These findings offer insights for smartwatch manufacturers and marketers to improve their products and develop more effective strategies to sustain smartwatch usage.